PENGGUNAAN MEDIA PERMAINAN KARTU DOMINO KOLOID UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK DI KELAS XI SMA NEGERI 1 TAPUNG HULU - marcella, Selly; Erna, Maria; ', Rini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The results of the study indicate that the use of colloid domino card game media can improving students learning achievement in class XI SMA Negeri 1 Tapung Hulu. Forms of this research was experimental research with radomized design of control group pretest-posttest. The population of this study were all students in class XI MIA SMA Negeri 1 Tapung Hulu. After being tested for normality and homogeneity tests, it determined the sample of the study were students of class XI MIA4 as an experimental class and students of class X1 MIA3 as the control class. Technique that used to data analysis was t-test with the criteria that the data processed in normal distribution. Based on the results of data analysis test, we obtained tcount>ttable is 3.38> 1.67, it meant that use of colloid domino card game media could improved learning achievement in the class XI SMA Negeri 1 Tapung Hulu. The category improvement of student achievement at experiment class was high category with a value of N-gain 0.71 while the control class included in the medium category with a value of N-gain of 0.60.Key Words: Learning Achievement, Colloid Domino Card Game